If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6n + 21 = 0 Reorder the terms: 21 + -6n = 0 Solving 21 + -6n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + -6n = 0 + -21 Combine like terms: 21 + -21 = 0 0 + -6n = 0 + -21 -6n = 0 + -21 Combine like terms: 0 + -21 = -21 -6n = -21 Divide each side by '-6'. n = 3.5 Simplifying n = 3.5
| r-25=49 | | 5y+12=42 | | 0.09xX=51.29 | | m-37=49 | | 44=h-33 | | 8/x=12/3 | | 8w-15w=35 | | 55=k-29 | | Y/3.5=10 | | 41=y+19 | | y-7=2.66(x-10) | | 4[4-(3-7x)]+2x=5(6x+3)-11 | | -1+2=2+3(2-1) | | 39+b=50 | | 3/8=x/1 | | c-3=13 | | 3(sin)x+1=(sin)x | | 10/1=x/2 | | 12x+9=8x+3+4x | | x+24=28 | | 62+5x=3(-x+3)-11 | | .09x+.11(x+9000)=2590 | | 2f=86 | | 33=-3f | | 2.5d+3.25=1+3.25 | | -7-13=9x+18-18x | | -70=7k | | 0=4/15y-28 | | 1/x=7/3 | | 7-8d=39 | | 1.08y=y+48 | | 3x-55+2x=5y |